2014
DOI: 10.1007/s11948-014-9615-z
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Biases and Compensatory Strategies Across Discipline, Rank, and Gender Among University Academics

Abstract: The study of ethical behavior and ethical decision making is of increasing importance in many fields, and there is a growing literature addressing the issue. However, research examining differences in ethical decision making across fields and levels of experience is limited. In the present study, biases that undermine ethical decision making and compensatory strategies that may aid ethical decision making were identified in a series of interviews with 63 faculty members across six academic fields (e.g. biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…"Academic leaders" may search effective ways for ethical codes to be used not only by faculty but also students and administrative staff. This passes through not just expecting them to internalize the codes on their own but explaining them the importance and details of the codes (Giorgini et al, 2015). As also Anderson et al (2013:246) suggested, organizational members should be involved both in execution and preparation of these codes for more inclusivity.…”
Section: Discussionmentioning
confidence: 99%
“…"Academic leaders" may search effective ways for ethical codes to be used not only by faculty but also students and administrative staff. This passes through not just expecting them to internalize the codes on their own but explaining them the importance and details of the codes (Giorgini et al, 2015). As also Anderson et al (2013:246) suggested, organizational members should be involved both in execution and preparation of these codes for more inclusivity.…”
Section: Discussionmentioning
confidence: 99%
“…6,39,40 and the dependence on specific factors. 17,41 We think that, for the exploration of abstract thinking, such as moral deliberation, reflective narration facilitates the presentation of ideas and opinions with greater coherence, without directing the response. 42,43 Furthermore, this approach may foster spontaneity and avoid restrictions or reductionisms of the type of response that could be given.…”
Section: Methodsmentioning
confidence: 99%
“…We chose the narrative response due to its ability to shed light on student behaviour patterns 6,39,40 . and the dependence on specific factors 17,41 42,43 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations